Rapid and Reliable Method for Identification of V. Cholera O1 and V. Cholera O139 Serotypes in Diarrheal Cases in Baghdad. - Auda, Ibtesam Ghadban (AL-Kindy College Medical Journal, 2013)
Backgrround:: Cholera is gastroenteritis caused by enterotoxin producing Vibrio cholera. Cholera is predominantly a waterborne disease especially in countries with inadequate sanitation. Several rapid methods have been developed and used to detect V. cholerae serotypes directly from stools. Objjecttiives:: to evaluate a rapid and accurate method for the diagnosis of cholera caused by V. cholerae O1 and O139 serogroups d to find the incidence of sporadic cases of cholera in Baghdad. Metthods:: Sixty four stool samples were collected from four hospitals in Baghdad. The age of patients ranging from two months to 12 years, 26 were females and 38 males. Immunochromatographic visual test for qualitative detection of O1 and /or O139 serogroups was used as well as routine culture procedure for isolation of V. cholerae. Resulltts:: Immunochromatographic visual test shows that, out of 64 stool samples only 16 was positive (23.4%). Fifteen of them belong to O1 serotype and one belong O139 serotype. Stool sample culture on alkaline peptone water and then on Thiosulfate Citrate Bile salts Sucrose (TCBS) agar enhance the growth of 11(68.75%) V. cholerae isolates out of 16 that were positive by using immunochromatographic visual test. Sensitivity of culture and immunochromatographic test was 68.75% and 100% respectively. Concllusiions:: V. cholerae O1 is more predominant than V. cholerae O139 among V. cholerae strains isolated from sporadic cases of cholera in Baghdad. Immunochromatographic test is rapid, accurate and more sensitive than culture method in recover V. cholerae strains.